Segmental variability of glucocorticoid induced electrolyte transport in rat colon. Issue 8 (August 1991) - Sandle, G I
Abstract : Recent studies suggest that the ability of glucocorticoids to reduce diarrhoea in active colitis may reflect their direct effects on distal colonic electrogenic Na+ transport and water absorption, as well as their anti-inflammatory action. To determine whether glucocorticoids induce similar changes in proximal colon, specific Na+ and K+ channel blockers (amiloride and tetraethylammonium chloride (TEA) respectively) were used to evaluate the cation transport properties of rat proximal and distal colon in vitro after three days treatment with the glucocorticoid agonist dexamethasone (600 micrograms/100 g/day). In the proximal colon, dexamethasone increased short circuit current (Isc) 2.3 fold (p less than 0.025) and total conductance (Gt) by 87% (p less than 0.015), but had negligible effects on the maximum activity of the basolateral membrane Na(+)-K+ pump and the baseline Na+ and K+ conductive properties of the apical membrane. Additional studies with diphenylamine-2-carboxylic acid (a Cl- channel blocker) suggested that the dexamethasone induced increases in Isc and Gt in proximal colon reflected stimulation of an electrogenic Cl- secretory process. In contrast, in the distal colon dexamethasone increased Isc 10 fold (p less than 0.025), Gt by 100% (p less than 0.015), and the maximum activity of the basolateral Na(+)-K+ pump by 200% (p less than 0.05), and induced substantial Na+ and K+ conductances in the apical membrane. These results indicate that dexamethasone stimulates electrogenic Na+ transport and water absorption to a significant degree only in the distal segment of rat colon. Thus in patients with active colitis, that part of the antidiarrhoeal action of glucocorticoids that reflects stimulation of electrogenic Na+ transport (and hence water absorption) may be restricted to the descending colon and rectum.